Reduced expression of brain-derived neurotrophic factor in mice deficient for pituitary adenylate cyclase activating polypeptide type-I-receptor - Zink, Mathias; Otto, Christiane; Zörner, Björn; Zacher, Christiane; Schütz, Günther; Henn, Fritz A.; Gass, Peter (Neuroscience letters, 2004)
In vitro pituitary adenylate cyclase activating polypeptide (PACAP) induces the expression of brain-derived neurotrophic factor (BDNF) via its specific receptor PAC1. Since BDNF has been implicated in learning paradigms and mice lacking functional PAC1 have deficits in hippocampus-dependent associative learning, we investigated whether PAC1 mutants show alterations in hippocampal expression of BDNF and its receptor TrkB. Semi-quantitative in situ-hybridization using exon-specific BDNF-probes revealed significantly reduced expression of the exon-III and exon-V-specific transcripts within the hippocampal CA3 region in PAC1-deficient mice. A similar trend was observed for the exon-I-specific transcript. The expression of the exon-III-specific transcript was also reduced within the dentate gyrus, while Trk B-expression did not differ between genotypes. Our data demonstrate that even in vivo PAC1-mediated signaling seems to play a pivotal role for the transcriptional regulation of BDNF.
Gesehen am 03.11.2020